1960
DOI: 10.2307/1539005
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Digestion and Hydrolytic Enzymes in the Phagocytes of Planarians

Abstract: It has been established that, in those species studied, intraluminar digestion does not occur in triclad flatworms (Willier, Hyman and Rifenburgh, 1925;Jennings, 1957), but that digestion takes place within food vacuoles in the phagocytic cells of the gastrodermis. A number of investigators have observed the disintegration of ingested food particles within these cells (Arnold, 1909;Saint-Hilaire, 1910;Jacek, 1917;von Levitzow, 1943), but the methods they employed did not permit elucidation of the mechanisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1963
1963
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…This confirms the reports of Rosenbaum and Rolon (1960) and of Jennings (1962b). The enzyme reaction product at this time was in the form of small granules which gradually increased in size and numbers until they filled the entire cell by the second day after ingestion of food.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This confirms the reports of Rosenbaum and Rolon (1960) and of Jennings (1962b). The enzyme reaction product at this time was in the form of small granules which gradually increased in size and numbers until they filled the entire cell by the second day after ingestion of food.…”
Section: Resultssupporting
confidence: 91%
“…The apparently greater intensity and longer persistence of acid phosphatase activity in our preparations is probably due to better enzyme preservation in frozen sections than in paraffin-embedded material. There is general agreement that acid phosphatase and other acid hydrolases are involved in the initial stages of digestion in food vacuoles (Rosenbaum and Rolon, 1960;Miiller et al, 1962;Jennings, 1962b) but the function of the alkaline phosphatase which appears some hours after the beginning of digestion is unknown. Jennings (1962b) suggests that it "may be concerned in the release of energy needed for secretion of the various enzymes and the absorption of the products of digestion from the vacuoles."…”
Section: Discussionmentioning
confidence: 99%
“…Acid phosphatase is thought to playa role in the initial stages of digestion of exogenous and endogenous materials [Rosenbaum & Rolon, 1960;Tomlinson & Warren, 1960;Jennings, 1962;Osborne & Miller, 1963;Ryder & Bowen, 1975]. The physiological function of alkaline phosphatase is unknown [Reid & Wilson, 1971;Saleem & Alikhan, 1974].…”
Section: Discussionmentioning
confidence: 99%
“…Although events in the intracellular digestion have been well studied at the levels of the light microscope (Willier et al, 1925;Kelley, 193 1;Rosenbaum & Rolon, 1960;Jennings, 1957Jennings, , 1962Jennings, , 1974 and transmission electron microscope (Ishii, 1972;Pascolini & Gargiulo, 1975;Bowen et al, 1974;Bowen, 1980;Garcia-Corrales & Gamo, 1988), details of ingestion through phagocytosis remain obscure, largely because of technical limitations in observation of sections. A previous TEM study (Ishii, 1972) showed that during phagocytosis the surfaces of the phagocytic cells appeared labyrinthine and pseudopodia seemed to differ in shape according to the nature of the food ingested.…”
Section: Introductionmentioning
confidence: 99%